Facilitating Students’ Speaking Task Using YouTube During Covid-19 Pandemic - Musliadi Musliadi; Reski Yusrini Islamiah Yunus; Muhammad Affan Ramadhana (Linguistics Initiative, 2021)
This study investigates students' perception of the use of YouTube to facilitate undergraduate students' speaking activities. The method used in this research is descriptive quantitative research. The sampling system is done randomly and takes 40 students as a sample. The questionnaire has two parts, followed by ten questions with five answer choices using a Likert scale covering strongly disagree to strongly agree. The result of the study shows that 80% of students access YouTube because YouTube is very interesting, 75% of students say YouTube is an easy media to access, 80% of students say YouTube can be used as a learning resource (80%), and 85% of students use YouTube as a medium for doing speaking tasks. The student response to the use of YouTube as the media of facilitating students' speaking tasks is very positive, where 72% of students stated they strongly agreed if the practice of speaking through YouTube was applied, and 20% of students agreed. In general, student responses in using YouTube to facilitate students speaking activities in distance learning during the Covid-19 pandemic are very positive.